Adolescents’ information and personal experiences regarding contraception - Savić, Nikola; Avramovic, Bojana; Jekic, Zoran; Andjelic, Sladjana; Bogdanovic Vasic, Slobodanka (Halo 194 Scientific Journal of Emergency Medicine, 2020)
Introduction: Contraception is the most favorable method in family planning. Prevention of unwanted pregnancy is important both from the aspect of preserving health, and from the aspect of wider preventive and social significance. Aim: To examine the information and personal experiences of adolescents regarding contraception. Methods: The research was conducted in the form of a cross-sectional study. As a research instrument, questionnaire for adolescents, which assesses their level of information about the importance of contraception, as well as personal experiences. The study included a sample of 120 students, the sample is intentional, the study was conducted at the Faculty of Health and Business Studies in Valjevo, Singidunum University, in the period April-May 2019. Participation in the study was voluntary and anonymous, the research was approved by the competent authorities of the institution. Results: Descriptive statistics methods were used in the analysis. Respondents in the observed sample were aged 19 to 23 years, the largest number of respondents are female (83%) and male 17%. Most of the respondents were informed about the methods of mechanical contraception and the use of condoms. The most commonly used contraceptive during sexual intercourse is a condom (63%). A large number of respondents (40%) believe that adolescents should be more informed about contraception. Conclusion: The results of the research indicate the need for a greater level of education about the methods and importance of contraception. It is necessary to intensify health education work in cooperation with health institutions, schools, higher education institutions and the entire community.